Production and Evaluation of Liquid Hydrocarbon Fuel from Thermal Pyrolysis of Virgin Polyethylene Plastics - Abbas, Ammar S.; Mohamed, Fahmi Abuelgasim (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
Pyrolysis of virgin polyethylene plastics was studied in order to produce hydrocarbon liquid fuel. The pyrolysis process carried out for low and high-density polyethylene plastics in open system batch reactor in temperature range of 370 to 450°C. Thermo-gravimetric analysis of the virgin plastics showed that the degradation ranges were between 326 and 495 °C. The results showed that the optimum temperature range of pyrolysis of polyethylene plastics that gives highest liquid yield (with specific gravity between 0.7844 and 0.7865) was 390 to 410 °C with reaction time of about 35 minutes. Fourier Transform Infrared spectroscopy gave a quite evidence that the produced hydrocarbon liquid fuel consisted mainly alkanes and the x-ray diffraction showed no sulfur in the produced hydrocarbon liquids.